Restoration of Cardiac Tissue Thyroid Hormone Status in Experimental Hypothyroidism: A Dose-Response Study in Female Rats - Weltman, Nathan Y. (Endocrine Society, 2013)
Thyroid hormones (THs) play a pivotal role in regulating cardiovascular homeostasis. To provide a better understanding of the coordinated processes that govern cardiac TH bioavailability, this study investigated the influence of serum and cardiac TH status on the expression of TH transporters and cytosolic binding proteins in the myocardium. In addition, we sought to determine whether the administration of T(3) (instead of T(4)) improves the relationship between THs in serum and cardiac tissue and cardiac function over a short-term treatment period. Adult female Sprague Dawley rats were made hypothyroid by 7 weeks treatment with the antithyroid drug 6-n-propyl-2-thiouracil (PTU). After establishing hypothyroidism, rats were assigned to 1 of 5 graded T(3) dosages plus PTU for a 2-week dose-response experiment. Untreated, age-matched rats served as euthyroid controls. PTU was associated with depressed serum and cardiac tissue T(3) and T(4) levels, arteriolar atrophy, altered TH transporter and cytosolic TH binding protein expression, fetal gene reexpression, and cardiac dysfunction. Short-term administration of T(3) led to a mismatch between serum and cardiac tissue TH levels. Normalization of serum T(3) levels was not associated with restoration of cardiac tissue T(3) levels or cardiac function. In fact, a 3-fold higher T(3) dosage was necessary to normalize cardiac tissue T(3) levels and cardiac function. Importantly, this study provides the first comprehensive data on the relationship between altered TH status (serum and cardiac tissue), cardiac function, and the coordinated in vivo changes in cardiac TH membrane transporters and cytosolic TH binding proteins in altered TH states.